2014
DOI: 10.1371/journal.pone.0110398
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Differences among Three Neurospora Species Reveal Genes Required for Sexual Reproduction in Neurospora crassa

Abstract: Many fungi form complex three-dimensional fruiting bodies, within which the meiotic machinery for sexual spore production has been considered to be largely conserved over evolutionary time. Indeed, much of what we know about meiosis in plant and animal taxa has been deeply informed by studies of meiosis in Saccharomyces and Neurospora. Nevertheless, the genetic basis of fruiting body development and its regulation in relation to meiosis in fungi is barely known, even within the best studied multicellular funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…Although orthologs of CPC-2 have been predicted in the genomes of several mushrooms, including model mushroom species (C. cinerea and S. commune) and cultivated mushrooms (Flammulina velutipes, Volvariella volvacea, Pleurotus ostreatus, Ganoderma lucidum, and Lentinus edodes) (Ohm et al, 2010;Stajich et al, 2010;Grigoriev et al, 2012;Bao et al, 2013;Park et al, 2014;Riley et al, 2014;Sakamoto et al, 2017), none of them has been functionally characterized. Similarly as that cpc-2 is up-regulated after crossing in N. crassa (Lehr et al, 2014), CPC-2 orthologs have an increased expression during fruiting body development in many mushroom species (Ohm et al, 2010;Yu et al, 2012;Cheng et al, 2013;Liu et al, 2015;Zhang et al, 2015;Sakamoto et al, 2017), suggesting that CPC-2 orthologs are likely involved in fruiting body development in these mushroom species. If it is true, CPC-2 ortholog encoding genes have potential to be a new group of reference genes for mushroom breeding.…”
Section: Introductionmentioning
confidence: 70%
“…Although orthologs of CPC-2 have been predicted in the genomes of several mushrooms, including model mushroom species (C. cinerea and S. commune) and cultivated mushrooms (Flammulina velutipes, Volvariella volvacea, Pleurotus ostreatus, Ganoderma lucidum, and Lentinus edodes) (Ohm et al, 2010;Stajich et al, 2010;Grigoriev et al, 2012;Bao et al, 2013;Park et al, 2014;Riley et al, 2014;Sakamoto et al, 2017), none of them has been functionally characterized. Similarly as that cpc-2 is up-regulated after crossing in N. crassa (Lehr et al, 2014), CPC-2 orthologs have an increased expression during fruiting body development in many mushroom species (Ohm et al, 2010;Yu et al, 2012;Cheng et al, 2013;Liu et al, 2015;Zhang et al, 2015;Sakamoto et al, 2017), suggesting that CPC-2 orthologs are likely involved in fruiting body development in these mushroom species. If it is true, CPC-2 ortholog encoding genes have potential to be a new group of reference genes for mushroom breeding.…”
Section: Introductionmentioning
confidence: 70%
“…First, a slight decrease in the secretion of melanin to the medium was evident. This may indicate improper melanin biosynthesis, which is part of successful fruiting body development (Lehr et al ., ). Moreover, the mob‐2a(Y117F,Y119F);Δmob‐2b double mutant was affected in female fertility.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous report, deletion of mob‐2a or mob‐2b was shown to not affect female fertility or ascospore abundance and shape (Maerz et al ., ). Although the functional link between MOB2A/B and sexual development has not been established, Lehr et al ., () found changes in mob‐2a and mob‐2b expression levels during perithecia formation. In this study, while using double mutants, in which mob‐2a was altered in a Δ mob‐2b background, we were able to expose a role for MOB2A/B during sexual development of the fungus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage-specific RNA editing also occurs during sexual reproduction in F. verticillioides. 13 Analysis with published RNA-seq data 16,17 showed that genome-wide A-to-I RNA editing also occurs in the model filamentous fungus Neurospora crassa 13 and its closely related species N. tetrasperma. However, because these published RNA-seq data of F. verticillioides and Neurospora species were un-stranded and generated from early sequencing platforms with short single end reads, they had high error rate and were not suitable for systematic identification of A-to-I editing sites.…”
mentioning
confidence: 99%